Problematika Ekonomi dalam Dakwah: Studi Realita Akses Pendidikan di Pondok Pesantren dan Dampak Biaya - Pamungkas, Yudha Catur; Hamidah, Lilik; Purnomo, Ryan (Jayapangus Press, 2024)
Islamic boarding schools are religious educational institutions that have an important role in shaping the character and morals of Indonesian society. However, in recent years, the rising cost of education has become one of the main challenges that hinder access for students, especially for underprivileged families. This study aims to analyze the impact of rising education costs on student access in Islamic boarding schools and identify solutions to overcome these problems. This study uses a qualitative approach with an analytical descriptive method. Data was collected through in-depth interviews with Islamic boarding school leaders, ustaz, students, and parents of students, as well as direct observation at several Islamic boarding schools. Documentation studies are also carried out to obtain information about cost management policies and programs run by pesantren. The results of the study show that the increase in operational costs of Islamic boarding schools, especially for infrastructure and modernization of education, is the main factor affecting the increase in education costs. In addition, family economic factors, the shift in social values from spiritualism to materialism, and the lack of government support have also worsened students' access to Islamic boarding schools. However, Islamic boarding schools are trying to find solutions by implementing zakat and infaq-based scholarship programs, as well as collaborating with philanthropic institutions. Some Islamic boarding schools also develop independent business units to support operations without burdening students. This study concludes that efficient management of education costs and innovation in education programs are essential to keep pesantren inclusive. Thus, pesantren can continue to be a pillar in da'wah and affordable Islamic education, as well as support the development of a better society.